Limnogeology in Southern South America: an overview (Latin American Journal of Sedimentology and Basin Analysis, 2021)
One of the major goals of Limnogeology is to provide clues on past Earth system environmental unevenness and feedbacks on longer time scales (100s-1,000s of years) than instrumental records, thus including periods with null or low anthropic influences on the environment. The multiproxy approach in the analysis of lake records allows to gain a wider overview than could be acquired from a single proxy data. Unlike the Northern Hemisphere, reconstructions of Late Pleistocene and Holocene environmental variability across Southern South America have been hampered by the paucity of complete and well-dated paleoclimate archives. However, last decades have been marked by a substantial increase of paleoclimatic research providing new data to analyze past climate variability from a regional perspective in Southern South America.This special issue include five articles applying a variety of proxy data (physical, chemical and biological) to elucidate climate and environmental changes on various time scales. Contributions cover a wide geographic distribution from the Antarctic Peninsula, Patagonia, Pampean region and NW Argentina up to the Río de la Plata Estuary. Results provide critical elements for further assessments of latitudinal paleo-circulation dynamics and hydroclimatic changes. The recent proliferation of limnogeological studies in Argentina and Uruguay evidence the reinforcement of regional research networks providing comparative and integrative analysis.